Management of abdominal wall recurrent subfascial seroma after pelvic surgery : SEROMA RECURRENCE MANAGEMENT - Damiani, Gianluca Raffaello; Lombardi, Claudio; Pulerà, Eleonora; Loizzi, Vera; Villa, Mario; Schonauer, Luca Maria; Cicinelli, Ettore (Acta Biomedica Atenei Parmensis, 2020)
Seroma is a serous fluid collection that accumulates in dead spaces, where tissue was attached to something before surgery. Abdominal seroma formation is a quite common complication after breast reconstruction with abdominal’s flaps or after an abdominoplasty procedure.The most frequently used method for decreasing early seroma frequency are the use of closed suction drains, ultrasonic dissection and sharp dissection, use of fibrine, and use of clip or ligation of vessels during the sur-gery. The management strategies consist of non-operative management, percutaneous drainage, or surgical drainage. With this paper we report a case of a subfascial seroma of the abdominal wall oc-curred in a 41 years old patient after laparotomy surgery for a voluminous pelvic serocele